Pharmacist gatekeeper interventions for suicide prevention: how evidence from developed countries support their role in low- and middle-income countries - Zhou, Zixiao; Mohamed, Fahim (Frontiers in Psychiatry, 2025)
BackgroundApproximately 70% of self-poisoning suicides occur in low- and middle-income countries (LMICs).The implementation of pesticide bans has significantly reduced the rate of pesticide self-poisoning in these regions; however, this has been accompanied by a shift toward an increased incidence of pharmaceutical poisoning, highlighting the importance of intervention strategies to prevent pharmaceutical self-poisoning in the future. This report summarizes the existing evidence on community pharmacist gatekeeper interventions aimed at reducing pharmaceutical suicide to discuss their complementary role with pesticide bans in LMICs.MethodsThe literature review identified studies published between April 2014 and April 2024 using multiple keywords related to “suicide,” “intervention,” “pharmacist” and “gatekeeper” in various library databases. Data were extracted into a table for analysis.ResultsOnly eight relevant studies were found during the search period, and none quantified the impact of pharmacy gate keeper interventions. Community pharmacists became more confident and willing to intervene after pharmacist gatekeeper training. They demonstrated positive attitudes and improved knowledge and skills in responding to suicidal intent. However, the evidence supporting community pharmacy gatekeeper interventions primarily comes from developed countries. Furthermore, the role of pharmacists in preventing suicide relies on frequent contact between suicidal individuals and pharmacies in developed countries.ConclusionPharmacy gatekeeper interventions can be implemented in LMICs as a complement to pesticide bans, provided they are modified and adapted to suit the specific context of these regions. Further research is essential to tailor and implement successful strategies from developed countries to address the unique challenges faced by LMICs.